Effects of isoflavone interventions on bone mineral density in postmenopausal women: a systematic review and meta-analysis of randomized controlled trials - K. Sansai (2020)
© 2020, International Osteoporosis Foundation and National Osteoporosis Foundation. Summary: Isoflavones have a structure similar to 17β-estradiol, so they may be useful to postmenopausal women in preventing bone loss related to estrogen deficiency. The present study integrated the findings from 63 randomized controlled trials and found that isoflavone interventions may have benefits in the prevention and treatment of menopause-related osteoporosis. Purpose: This study aimed to determine the efficacy of isoflavone interventions on bone density outcomes and the safety of isoflavone interventions in postmenopausal women by means of systematic review and meta-analysis. Methods: A systematic search was performed on three databases (PubMed, Scopus, and Cochrane Library). Included studies were limited to randomized controlled trials (RCTs) assessing the effects of isoflavone intervention on bone mineral density (BMD) in postmenopausal women. Mean difference (MD) in BMD or relative risk for adverse outcomes was used as a summary effect measure; pooled-effect estimates were calculated using a random-effects model. Results: A total of 63 RCTs, involving 6427 postmenopausal women, were included in the meta-analysis. Statistically significant differences in BMD at the last follow-up visit between the two groups (isoflavones vs. control) were found at the lumbar spine (MD = 21.34 mg/cm2, 95% CI = 8.21 to 34.47 mg/cm2, p = 0.001), the femoral neck (MD = 28.88 mg/cm2, 95% CI = 15.05 to 42.71 mg/cm2, p ' 0.0001), and the distal radius (MD = 19.27 mg/cm2, 95% CI = 5.65 to 32.89 mg/cm2, p = 0.006). The positive effects in improved BMD were primarily associated with two formulations, i.e., genistein 54 mg/day and ipriflavone 600 mg/day. Isoflavone interventions were generally safe and well tolerated. Conclusion: Isoflavone interventions, genistein (54 mg/day) and ipriflavone (600 mg/day) in particular, have beneficial effects on BMD outcomes and are safe in postmenopausal women. They may be considered as a complementary or alternative option in the prevention and treatment of menopause-related osteoporosis.